2014
DOI: 10.1016/j.yrtph.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Testing the coherence between occupational exposure limits for inhalation and their biological limit values with a generalized PBPK-model: The case of 2-propanol and acetone

Abstract: a b s t r a c tThe coherence between occupational exposure limits (OELs) and their corresponding biological limit values (BLVs) was evaluated for 2-propanol and acetone. A generic human PBPK model was used to predict internal concentrations after inhalation exposure at the level of the OEL. The fraction of workers with predicted internal concentrations lower than the BLV, i.e. the 'false negatives', was taken as a measure for incoherence. The impact of variability and uncertainty in input parameters was separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The magnitude of the reduction in the range of reconstructed air concentrations depends on the modeled chemical and the moment of data collection. In previous studies, the importance of human physiological data has also been demonstrated, especially during and shortly after exposure (Huizer et al, 2012(Huizer et al, , 2014. The shorter after the incident measurements are performed, the more relevant it is to collect individual physiological data.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The magnitude of the reduction in the range of reconstructed air concentrations depends on the modeled chemical and the moment of data collection. In previous studies, the importance of human physiological data has also been demonstrated, especially during and shortly after exposure (Huizer et al, 2012(Huizer et al, , 2014. The shorter after the incident measurements are performed, the more relevant it is to collect individual physiological data.…”
Section: Discussionmentioning
confidence: 98%
“…The model is briefly described here (see also Fig. 1), while a more detailed model description can be found in Huizer et al (2012) and Huizer et al (2014). BioNormtox model contains 10 biological compartments.…”
Section: Bionormtox Modelmentioning
confidence: 99%
See 1 more Smart Citation